The Knowledge and Attitude of the Parents of Children with ADHD toward Methylphenidate (Ritalin) - Sanaz Noroozi; Mostafa Farahbakhsh; Mohammad Taha Saadati Rad; Shahrokh Amiri; Farinaz Saeedi (Shiraz University of Medical Sciences, 2023)
Background: Methylphenidate is an important drug treatment for attention-deficit/hyperactivity disorder (ADHD). Parents' knowledge of the drug predicts their adherence to this treatment and active participation in the therapeutic interventions. The present study aimed to evaluate the knowledge and attitude of the parents of children with ADHD, who referred to the child and adolescent psychiatry clinic of Tabriz University of Medical Sciences, regarding methylphenidate (Ritalin).Methods: This descriptive, cross-sectional study was performed on 300 parents during 2019-2020. The subjects were selected through convenience sampling. Data were collected using the socioeconomic status questionnaire and a researchermade questionnaire, which encompassed the two sections of demographic information and parents' attitudes, knowledge and performance. The validity and reliability of the tool were confirmed. Data analysis was performed in SPSS version 16 using descriptive statistics, Chi-square, and t-test.Results: The mothers played a more significant role in the care of children with ADHD compared to the fathers. Significant correlations were observed between the parents' knowledge, attitude, and performance with Ritalin consumption, and the knowledge score of the parents was low (46.6%), confirming their need for education in this regard. Meanwhile, 52.86% of the parents had a moderate knowledge level, and only 1% had excellent knowledge regarding the drug. Overall, the parents considered methylphenidate a more effective drug for ADHD compared to other medications. However, 84% of the parents were concerned about their children's Ritalin addiction. According to the results, mothers played a more significant role in the treatment of children with ADHD compared to the fathers.Conclusion: According to the results, parents' participation in the treatment of children and adolescents with ADHD as a supporter and provider of methylphenidate had a positive effect in this regard. Therefore, supporting and improving the knowledge and attitude of parents could improve their perception of methylphenidate consumption by their ADHD children, thereby enhancing the prognosis of the patients.